The management of acne vulgaris in primary care: a cohort study of consulting and prescribing patterns using the Clinical Practice Research Datalink. (1st January 2017) - Francis, N.A.; Entwistle, K.; Santer, M.; Layton, A.M.; Eady, E.A.; Butler, C.C.
Summary: Background: Effective management of acne vulgaris in primary care involves support (usually provided over a number of consultations) and prescription of effective treatments. However, consulting and prescribing patterns for acne in primary care are not well described. Objectives: To describe the rate of primary‐care consultations and follow‐up consultations; prescribing patterns, including overall use of acne‐related medications (ARMs); and initial and follow‐up prescription for acne vulgaris in the U.K. Methods: U.K. primary‐care acne consultations and prescriptions for ARMs were identified in the Clinical Practice Research Datalink. Annual consultation rates (between 2004 and 2013) by age and sex, new consultations and consultations in the subsequent year were calculated, along with prescribing trends – during a new consultation and over the subsequent 90 days and year – using the number of registered patients as the denominator. Results: Two‐thirds (66·1%) of patients who had a new acne consultation had no further acne consultations in the subsequent year. Overall 26·7%, 24·9%, and 23·6% and 2·8% of patients were prescribed no ARM, an oral antibiotic, a topical antibiotic or an oral plus topical antibiotic, respectively, during a new acne consultation. In total 60·1% and 38·6% of patients prescribed an ARM received no further ARM prescriptions in the following 90 days and 1 year, respectively, despite most prescriptions being for 2 months or less. Prescribing rates for lymecycline and topical combined clindamycin and benzoyl peroxide increased substantially between 2004 and 2013. There were no important changes in consultation rates between 2004 and 2013. Conclusions: These data suggest that patients with acne are receiving a suboptimal initial choice of ARMs, longitudinal care and prescribing.